Association between Omentin Levels and Insulin Resistance in Pregnancy - Aktas, G.; Alcelik, A.; Ozlu, T.; Tosun, M.; Tekce, B. K.; Savli, H.; Tekce, H.; Dikbas, O. (Experimental and Clinical Endocrinology & Diabetes, 2014)
Omentin is a new adipokine secreted mainly from visceral adipose tissue. Serum omentin is found to be reduced in patients with impaired glucose tolerance, type 2 diabetes mellitus, obesity and insulin resistant states. Despite the fact that pregnancy is also characterized with hyperinsulinemia, literature is lacking about data of omentin levels and its association with insulin resistance in pregnant women. We aimed to evaluate the association of omentin levels and insulin resistance in pregnant women and to compare these levels with those of non-pregnant, non-diabetic women.Uncomplicated pregnant women who admit to our outpatient clinics for routine follow-up were included in the study group. Non-pregnant women without diabetes mellitus were served as control group. Fasting glucose, insulin, omentin levels and HOMA IR were recorded. SPSS 15.0 for Windows was used for statistical analysis.There were 36 pregnant women in the study group and 37 healthy, non-pregnant women in the control group. Serum omentin and fasting glucose levels were significantly decreased and fasting insulin was significantly increased in the study group compared to control group.Omentin might be an indicator of insulin resistance in pregnant women. Larger prospective studies are needed to claim whether omentin can have a clinical use for diagnosis of gestational diabetes mellitus.
Keywords: omentin; insulin resistance; pregnancy